Genomic profiling of cell-free DNA from dogs with benign and malignant tumors - Hongchao Du; Wenfeng Liu; Yunfei Li; Lijuan Zhang; Fangfang Jiang; Dandan Zhu; Jingshuai Li; Pan Hu; Ningning Yan; Mao Mao; Shiyong Li (BMC Research Notes, 2024)
Abstract Objective Cancer is currently the most common cause of death in adult dogs. Like humans, dogs have a one-third chance of developing cancer in their lifetime. We used shallow whole-genome sequencing (sWGS) to analyze blood cell-free DNA (cfDNA) from four tumor-bearing dogs (one with benign and three with malignant tumors) and 38 healthy dogs. Results Similar to the results observed in the healthy dogs, no copy number aberration (CNA) was detected in the dog with benign lipomas, and the distribution of cfDNA fragment size (FS) closely resembled that of the healthy dogs. However, among the three dogs diagnosed with malignant tumors, two dogs exhibited varying degrees and quantities of CNAs. Compared to the distribution of FS in the healthy dogs, the cancer dogs exhibited a noticeable shift towards shorter lengths. These findings indicated that CNA and FS profiles derived from sWGS data can be used for non-invasive cancer detection in dogs.